Non-linear model predictive control schemes with application on a 2 link vertical robot manipulator. (October 2016) - Wilson, Jacob; Charest, Meaghan; Dubay, Rickey
Abstract: The industrial requirements for controllers able to perform tasks in the presence of plant nonlinearities are growing. In addition, an increase in industrial computation power is allowing the implementation of more complex control algorithms in the fast processing industry. In this investigation three different nonlinear model predictive control algorithms are tested and evaluated in simulation and experimentally. The methodologies are adaptive nonlinear model predictive control (nMPC), PID based nMPC (PIDnMPC), and a novel simplified nMPC (SnMPC). These are tested in simulation with an inverted pendulum, a Van der Pol oscillator, and a planar 2-link vertical robotic arm. The controllers are tested experimentally using a fabricated planar 2-link vertical robotic arm apparatus. A comparison of the different algorithms is made with special attention to trajectory tracking, computational complexity and transient response dynamics. Abstract : Highlights: Three non-linear MPC Algorithms are developed to control fast systems, nMPC, PIDnMPC and SnMPC. The algorithms are tested in simulation using three non-linear models. The controller features are discussed and future directions of study are suggested.